2020
DOI: 10.4081/gh.2020.795
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the socio-environmental vulnerability of black and Caucasian pregnant women in Salvador, Bahia, Brazil to the occurrence of microcephaly associated with the congenital syndrome of zika virus

Abstract: To understand the occurrence of the Congenital Zika Syndrome (CZS), the living conditions of pregnant individuals must be considered in order to identify factors and areas of risk. An intersectional approach provides an understanding of the vulnerabilities to which Black women are subjected. To that end, we present an overview of the spatio-temporal distribution of confirmed cases of microcephaly associated with CZS during the 2015-2016 period in Salvador, Bahia, Brazil based on a survey of Black and Caucasian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Additionally, the spatial analysis unit of the present study, which encompassed different social strata, might have made these indicators less discriminatory between municipalities. Other studies that analysed the Northeast and Southeast regions of Brazil found associations between the incidence of ZIKV and factors such as population density, human development index, primary care coverage, violence rate, average household income, and race, thereby reinforcing the association of the social determinants of health with the dispersion of ZIKV and the worsening of congenital cases [ 28 , 67 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the spatial analysis unit of the present study, which encompassed different social strata, might have made these indicators less discriminatory between municipalities. Other studies that analysed the Northeast and Southeast regions of Brazil found associations between the incidence of ZIKV and factors such as population density, human development index, primary care coverage, violence rate, average household income, and race, thereby reinforcing the association of the social determinants of health with the dispersion of ZIKV and the worsening of congenital cases [ 28 , 67 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian studies show a heterogeneous geographical distribution of ZIKV infection and microcephaly [ 23 26 ], potentially explained by climatic factors, vector abundance, and unfavourable socioeconomic conditions [ 27 29 ]. Epidemiological studies have mostly been conducted in areas with higher incidences of acute ZIKV disease and of microcephaly [ 27 , 28 , 30 ]. However, there is little known about the regions that were less affected in the first wave, such as the Central-West region.…”
Section: Introductionmentioning
confidence: 99%
“…Essa diversificação de funções sociais não foi estendida à mulher negra, mas reforçou desigualdades de classe e de raça entre as mulheres, pois as atividades que não foram culturalmente trabalhadas dentro do ambiente doméstico, com vistas a aniquilar a divisão sexual do trabalho, foram transferidas para mulheres negras, reforçando a presença desse grupo em ambiente privado, na posição, por exemplo, de empregadas domésticas 33 . Diferenças entre esses grupos também são vistas no campo da saúde 34,35 ou nas taxas de violência 36 . Essas desigualdades negam a cidadania e limitam a ascensão social da mulher negra, com consequências negativas à garantia dos seus direitos, entre eles o direito à alimentação.…”
Section: Renda Familiar Per Capitaunclassified
“…Mothers live in extreme socioeconomic vulnerability (31) , low education (22) with worse living conditions indices when they are black (23) . More than half of them live in peripheral areas under precarious conditions, such as wooden houses located in hillside regions with risk of collapse, absence of garbage collection and sanitation, with constant presence of mosquitoes (24)(25) .…”
Section: Access To Social Protection Rights Goods and Servicesmentioning
confidence: 99%